Religion and secularism in Nigeria: the effect of compulsory dress codes in the educational system on the right to practice religion (2021)
Though Nigeria is regarded as a secular state, there are two major religions which are predominantly practiced. Religious sentiments have permeated the societal space in Nigeria and often times the ardent practice and observance of religious tenets lead to perennial conflicts with governmental policies. It is one of the fundamental precepts of human rights that the religious belief of individuals should be respected, therefore the provision for the protection of right to religion in the national laws and some international instruments. The education system requires specific dress codes which must be observed. It is against this backdrop that this paper examines the right to practice religion in Nigeria and the obvious conflicts between this practice and policies in the Nigerian education system particularly at primary and post-primary school levels. The paper addresses the scope of the right to practice one’s religion under the law vis-à-vis governmental policies in educational institutions.